Cytoprotective roles of epigallocatechin gallate and resveratrol on staurosporine-treated mesenchymal stem cells in in vitro culture - Burczak Arkadiusz (Sciendo, 2021)
Introduction: There are many scientific reports on the beneficial effects of epigallocatechin gallate and resveratrol on the human body, e.g. antioxidant properties, a protective effect on the circulatory system and reduction of inflammation.